The image of the poet Mihai Eminescu in the literary dictionaries - Tcacenco, Petra Denisa (Journal of Education Culture and Society, 2020)
Mihai Eminescu is known as the Romanian national poet, the most important writer of the XIXͭʰ century in Romanian literature, whose writings have been intensely interpreted since his poetic debut. Therefore, this paper proposes a study of the way the literary dictionaries build the image of “the national poet”. This identity construct is significant to our investigation because it influences the interpretation of the poet figure through history. In order to have a wider view of the problem, we consulted a series of literary dictionaries and, also, dictionaries for students use to see how the figure of Eminescu is taught in schools. Moreover, we did not put aside foreign dictionaries, which bring a more objective perspective to the issue. The majority of Romanian dictionaries alter the poet’s portrait in favor of a “national construct”, created partly by the use of rhetoric figures. Another way of composing him a deformed image is accomplished by writing subjective and opaque interpretation of his poems. Consequently, such hermeneutics focuses on developing a myth that reflects mainly the way Romanians as nation want to be recognized and remembered.